The effect of structured inquiry-based teaching on biology students achievement test - Lee, Tze Jiun; Kamarudin, Nurzatulshima; Talib, Othman; Hassan, Aminuddin (Global Academic Exellence, 2018)
The purpose of this study was to investigate the effects of structured inquiry-based teaching (SIBT) on Biology students’ higher order level achievement test. Two classes of Form 4 students (n= 64) from two public school secondary mixed schools in Kuala Lumpur, Malaysia, were chose for the study. This study used a quasi-experiment with pretest-post-test design. One group was assigned as experimental group (SIBT) whereas the other group was assigned to practice traditional teaching (TT). After eight weeks experimental study, post test was administrated for both groups. The results showed that students who were instructed through SIBT were achieved higher score than traditional instruction group.